2003
DOI: 10.1128/cdli.10.5.797-801.2003
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Responses to Escherichia coli O157 and Other Lipopolysaccharides in Healthy Children and Adults

Abstract: In Mexico, diarrheal disease due to different serotypes of Escherichia coli is highly prevalent, with only sporadic isolation of O157 non-H7 strains. This could be due to exposure to the O157 or related E. coli lipopolysaccharide (LPS), such as O7 or O116, at an early age. By using enzyme-linked immunosorbent assay (ELISA) and Western blotting, the present study analyzed 605 serum samples from Mexican adults and infants without clinical symptoms of disease for the presence of antibodies to these three E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 40 publications
(31 reference statements)
2
16
0
Order By: Relevance
“…Antibodies to LPS O157 in healthy adults and children may be acquired by contact with O157 non-H7 E. coli and other serogroups such as O7 or O116 E. coli or strains with cross-reacting LPS and by placental transfer or breastfeeding in infants. 8 Cross-reactions among antibodies reactive with common epitopes of different LPS were also confirmed in bovine serum samples. 19 Our results suggest that there is a gradual acquisition of anti-LPS antibodies with increasing age, with the increase in antibody values occurring earlier for IgM antibodies than for IgG antibodies, probably simultaneously with the development of total serum immunoglobulin concentrations.…”
Section: Discussionmentioning
confidence: 74%
“…Antibodies to LPS O157 in healthy adults and children may be acquired by contact with O157 non-H7 E. coli and other serogroups such as O7 or O116 E. coli or strains with cross-reacting LPS and by placental transfer or breastfeeding in infants. 8 Cross-reactions among antibodies reactive with common epitopes of different LPS were also confirmed in bovine serum samples. 19 Our results suggest that there is a gradual acquisition of anti-LPS antibodies with increasing age, with the increase in antibody values occurring earlier for IgM antibodies than for IgG antibodies, probably simultaneously with the development of total serum immunoglobulin concentrations.…”
Section: Discussionmentioning
confidence: 74%
“…Therefore measurement of antibodies against LPS by serological assays such as ELISA and Western Blot (WB) has been widely used for diagnosis of a number of illnesses caused by gram-negative organisms including E. coli O157:H7 [7][9]. However, at the time of the outbreak an assay able to give evidence of the antibody status after an infection with the outbreak strain was not available.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation rates have been widely reported (Naylor et al, 2005), with levels of 1.8 % in Japan (Miyao et al, 1998), 1.9 % in Australia (Cobbold & Desmarchelier, 2000) and from 0 to 7.4 % in the USA (Faith et al, 1996). In Mexico, serotyping data of approximately 16 000 E. coli isolates collected over the past 20 years have shown an isolation frequency of 1 % for E. coli O157 strains (Navarro et al, 2003). In another study in Mexico, Callaway et al (2004) showed an isolation frequency of 1.25 % for E. coli O157 in cattle and 2.1 % in swine.…”
Section: Introductionmentioning
confidence: 99%